Neverland is an evolutionally conserved Rieske-domain protein that is essential for ecdysone synthesis and insect growth. - Yoshiyama, T.; Namiki, T.; Mita, K.; Kataoka, H.; Niwa, R. (Development, 2006)
Steroid hormones mediate a wide variety of developmental and physiological events in multicellular organisms. During larval and pupal stages of insects, the principal steroid hormone is ecdysone, which is synthesized in the prothoracic gland (PG) and plays a central role in the control of development. Although many studies have revealed the biochemical features of ecdysone synthesis in the PG, many aspects of this pathway have remained unclear at the molecular level. We describe the neverland (nvd) gene, which encodes an oxygenase-like protein with a Rieske electron carrier domain, from the silkworm Bombyx mori and the fruitfly Drosophila melanogaster. nvd is expressed specifically in tissues that synthesize ecdysone, such as the PG. We also show that loss of nvd function in the PG causes arrest of both molting and growth during Drosophila development. Furthermore, the phenotype is rescued by application of 20-hydroxyecdysone or the precursor 7-dehydrocholesterol. Given that the nvd family is evolutionally conserved, these results suggest that Nvd is an essential regulator of cholesterol metabolism or trafficking in steroid synthesis across animal phyla.